Small-Conductance Ca2+-Activated K+ Channels 2 in the Hypothalamic Paraventricular Nucleus Precipitates Visceral Hypersensitivity Induced by Neonatal Colorectal Distension in Rats - Ji, Ning-Ning; Du, Lei; Wang, Ying; Wu, Ke; Chen, Zi-Yang; Hua, Rong; Zhang, Yong-Mei (Frontiers in Pharmacology, 2021)
Visceral hypersensitivity is one of the pivotal pathophysiological features of visceral pain in irritable bowel syndrome (IBS). Small-conductance Ca2+-activated K+ channel (SK) is critical for a variety of functions in the central nervous system (CNS), nonetheless, whether it is involved in the pathogenesis of visceral hypersensitivity remain elusive. In this study, we examined mechanism of SK2 in hypothalamic paraventricular nucleus (PVN) in the pathogenesis of visceral hypersensitivity induced by neonatal colorectal distension (CRD). Rats undergoing neonatal CRD presented with visceral hypersensitivity as well as downregulated membrane SK2 channel and p-PKA. Intra-PVN administration of either the membrane protein transport inhibitor dynasore or the SK2 activator 1-EBIO upregulated the expression of membrane SK2 in PVN and mitigated visceral hypersensitivity. In addition, 1-EBIO administration reversed the increase in neuronal firing rates in PVN in rats undergoing neonatal CRD. On the contrary, intra-PVN administration of either the SK2 inhibitor apamin or PKA activator 8-Br-cAMP exacerbated the visceral hypersensitivity. Taken together, these findings demonstrated that visceral hypersensitivity is related to the downregulation of membrane SK2 in PVN, which may be attributed to the activation of PKA; pharmacologic activation of SK2 alleviated visceral hypersensitivity, which brings prospect of SK2 activators as a new intervention for visceral pain.